2020
DOI: 10.1163/22941932-00002106
|View full text |Cite
|
Sign up to set email alerts
|

Direct exposure to solar radiation causes radial growth eccentricity at the beginning of the growing season in Robinia pseudoacacia

Abstract: Our study investigated the effect of stem temperature increase on xylem formation in Robinia pseudoacacia tree-trunks, caused by direct exposure to solar radiation. It is important to determine factors which may improve the concentricity of deposited wood tissue and intensify xylogenesis because a strong irregularity of wood tissue deposited in the radial direction in mature trees of R. pseudoacacia reduces the commercial value of the wood. Samples of vascular cambium along with adjacent tissues were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…According to this concept radial tensile stress in the cambium would change to compressive stress later in the growing season (Hejnowicz, 1997 ; Kwiatkowska & Nakielski, 2011 ). However, the study of Robinia pseudoacacia xylogenesis (Miodek et al ., 2020 ) revealed that the phloem within the stem seems to collapse much too early to explain the growth of first broad vessel elements of earlywood (Fig. 6 ) – phloem showed a reduced radial dimension in March, compared to the radial dimension observed in August of the previous year.…”
Section: Mechanical Conditions In the Vascular Cambium And Developing...mentioning
confidence: 98%
“…According to this concept radial tensile stress in the cambium would change to compressive stress later in the growing season (Hejnowicz, 1997 ; Kwiatkowska & Nakielski, 2011 ). However, the study of Robinia pseudoacacia xylogenesis (Miodek et al ., 2020 ) revealed that the phloem within the stem seems to collapse much too early to explain the growth of first broad vessel elements of earlywood (Fig. 6 ) – phloem showed a reduced radial dimension in March, compared to the radial dimension observed in August of the previous year.…”
Section: Mechanical Conditions In the Vascular Cambium And Developing...mentioning
confidence: 98%
“…Due to the highly ordered arrangement of its components, such structure allows for precise anatomical analysis of the course of intrusive growth of initials and wood fibres 37 . Key factor taken into account while choosing this species as the main object of the study was its growing economic importance outside the area of natural distribution 31 , 38 due to its high adaptive potential, especially in the context of emerging environmental threats.…”
Section: Methodsmentioning
confidence: 99%
“…Due to (1) the newly proposed role of symplastic growth in mathematical modelling of expansion of cambial circumference, and (2) the fact that previously mentioned studies challenging a wide-spread view that intrusive growth leads to an increase in cambial circumference were of qualitative type, a quantitative analysis of influence of intrusive growth on tangential dimension of fragment of tissue within which cambial rearrangement takes place is necessary. The main goal of this study is to further elucidate, both quantitatively and qualitatively, the mechanism of intrusive growth of cambial initial cells on the example of Robinia pseudoacacia L.—a tree species of growing economic potential in Europe 31 . It is also one of the most highly invasive alien species threatening biodiversity, which, given the anticipated climate changes, may become an increasing ecological and economic problem 32 35 .…”
Section: Introductionmentioning
confidence: 99%
“…The study was performed on black locust (Robinia pseudoacacia L.)-a deciduous, ring-porous species (Miodek et al 2020). Examined tree with a circumference of ca.…”
Section: Plant Materialsmentioning
confidence: 99%